Dynamics of defects accumulation during hydrogen charge of titanium and stainless steel; Korus 2001; Vol. 2 - Chernov I. P. Ivan Petrovich; Cherdantsev Yu. P. Yuriy Petrovich; Lider A. M. Andrey Markovich; Garanin G. V. Georgy Viktorovich; Nikitenkov N. N. Nikolai Nikolaevich (2001, 2001)
The hydrogen influence on dynamics of defect formation in VT1-0 titanium and 316-stainless steel was studied. The electrolytic charging by hydrogen in LiOH+H2O solution was performed at a current density 0.5-1 A/cm2. Optical and raster electron microscopy, have revealed a considerable amount of defects on a sample surface which have appeared after enrichment with hydrogen. For stainless steel, as opposed to titanium, at time of hydrogen charging less than 1 hour and current densities up to 1 A/cm2 surface erosion is not detected. The study of metal bulk defects was performed by positron annihilation method. The results of measurement of positron lifetime have shown that at about 150 microns depths the fundamental contribution (up to 90 %) is determined by single vacancies and dislocation. The hydrogen in stainless steel is actively connecting with carbides on grain boundaries. The obtained results allow making a conclusion that bulk destruction of metal grains does not occur.